Effect of environmental corporate social responsibility on green attitude and norm activation process for sustainable consumption: airline versus restaurant - Han, Heesup; Chua, Bee Lia; Ariza Montes, Antonio; Untaru, Elena Nicoleta (Wiley, 2020)
The major aim of this research was to develop theoretical frameworks clearly explicating airline and restaurant customers' decision formation for eco-friendly products. Using a quantitative approach, we successfully broadened the norm activation theory by integrating environmental corporate social responsibility (CSR) and attitude toward the behavior. In addition, the theory was effectively deepened by taking the influence of product type (airline vs. restaurant) into account. The developed conceptual frameworks satisfactorily explained the variance in eco-friendly purchase intention for airline products and for restaurant products, respectively. The mediating effect of attitude, ascribed responsibility, and personal moral norm was uncovered. Additionally, a salient contribution of attitude toward eco-friendly product use in inducing intention for both airline and restaurant groups was found.